Microemulsion-assisted Zinc Oxide Synthesis: Morphology Control and Its Applications in Photoanodes of Dye-Sensitized Solar Cells. (20th August 2016) - Lee, Chuan-Pei; Li, Chun-Ting; Fan, Miao-Syuan; Li, Sie-Rong; Huang, Yi-June; Chang, Ling-Yu; Tseng, Chuan-Ming; Sun, Shih-Sheng; Lin, Jiang-Jen; Ho, Kuo-Chuan
Graphical abstract: Highlights: ZnO crystals with various morphologies are synthesized by microemulsion technique. ZnO crystals show structures of hexagonal club, nanoparticle, and hexagonal plate. An efficient organic sensitizer, DJ104 dye, is synthesized for the ZnO-based DSSCs. Sub-micro ZnO hexagonal club and hexagonal plate are useful for light scattering. A cell efficiency of 7.40% is achieved for the DSSC with DJ104-sensitized ZnO film. Abstract: Zinc oxide (ZnO) crystals with structures of hexagonal club (HC), nanoparticle (NP), and hexagonal plate (HP) are synthesized via microemulsion technique by using the surfactants of cationic cetylmethylammonium bromide (CTAB), nonionic Triton ® X-100, and anionic docusate sodium (AOT), respectively, and they are used for the photoanodes of dye-sensitized solar cells (DSSCs). Phase diagrams are constructed in mapping the compositions of the microemulsions to guide the synthesis of ZnO crystals. All the synthesized ZnO crystals exhibited wurtzite crystal phase of ZnO in their X-ray diffraction (XRD) patterns, and their morphologies and structures were investigated by scanning electron microscopy (SEM) and high-resolution transmission electron microscopy (HR-TEM), respectively. The sub-micro sized HC and HP ZnO crystals are meritorious in the present work as large particles are effective for light-scattering in the photoanode; the nano-sized NP ZnO crystal is meritorious in the present work as small particles are effective for dye adsorption in the photoanode of DSSCs. By using the photoanodes with bi-layer NPs/HPs and NPs/HCs ZnO films for the ZnO-based DSSCs with a novel organic dye (coded DJ149), we obtained good cell efficiencies of 7.40% and 6.95%, respectively. Incident photon-to-current conversion efficiency (IPCE) curves, and UV–vis reflectance spectra are also used to substantiate the results.